OVERVIEW OF THE RELATIONSHIP BETWEEN THE ITALIAN CONSTITUTIONAL COURT AND EU LAW, WITH PARTICULAR REFERENCE TO THE ITALIAN CONSTITUTIONAL COURT’S APPROACH TO RENEWABLE ENERGY POLICY (EU and comparative law issues and challenges series (ECLIC), 2018)
The paper aims to analyse how European Union law and the jurisprudence of the EU Court of Justice currently influence the interpretation of the Italian Constitution and, at the same time, whether there are still limits to the ‘internationalisation’ and ‘Europeanisation’ of national constitutional laws that are relevant for the analysis of the Constitution. Until 2001, there was no mention in the Italian Constitution of the European Union or the interaction between the national and the European legal system. Following the 2001 reform, a reference to European Union law was introduced in Article 117 of Italian Constitution, and the relationship between the Italian Constitutional Court and EU law changed entirely. For many years, it had been based on the theory of counter-limits (Italian Constitutional Court judgments in Frosini n. 173/1973 and Granital n. 170, 5 June 1984). As an example of the new relationship mentioned above, we use the Italian Constitutional Court’s approach to renewable energy policy.